Low-cost and prototype-friendly method for biocompatible encapsulation of implantable electronics with epoxy overmolding, hermetic feedthroughs and P3HT coating - Novák, Marek; Rosina, Jozef; Bendová, Hana; Kejlová, Kristina; Vlková, Alena; Rucki, Marian; Svobodová, Lada; Gürlich, Robert; Hajer, Jan (Scientific reports, 2023)
The research of novel implantable medical devices is one of the most attractive, yet complex areas in the biomedical field. The design and development of sufficiently small devices working in an in vivo environment is challenging but successful encapsulation of such devices is even more so. Industry-standard methods using glass and titanium are too expensive and tedious, and epoxy or silicone encapsulation is prone to water ingress with cable feedthroughs being the most frequent point of failure. This paper describes a universal and straightforward method for reliable encapsulation of circuit boards that achieves ISO10993 compliance. A two-part PVDF mold was machined using a conventional 3-axis machining center. Then, the circuit board with a hermetic feedthrough was placed in the mold and epoxy resin was injected into the mold under pressure to fill the cavity. Finally, the biocompatibility was further enhanced with an inert P3HT polymer coating which can be easily formulated into an ink. The biocompatibility of the encapsulants was assessed according to ISO10993. The endurance of the presented solution compared to silicone potting and epoxy potting was assessed by submersion in phosphate-buffered saline solution at 37 °C. The proposed method showed superior results to PDMS and simple epoxy potting.
Keywords: epoxidové pryskyřice; Epoxy Resins; voda; Prostheses and Implants; silikony; elektronika; Silicones; Electronics; protézy a implantáty; Water